The Extent Of Application Of The Algerian Standard For Auditing 230 “ Audit Documents” By The Auditors - Farouk Senouci Sid Ahmed; Larbi Ghrissi (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The aim of this research paper is to assese the extent to which Algerian Auditing Standard No 230, labeled as “Audit Documentation”, is implemented by external auditors in Algeria. In pursuit of the study’s overarching goals, we distributed a questionnaire to a sample of professionals to collect necessary data and analyzed it using SPSS24. This study reveals that the majority of external auditors are not fully acquinted with the provisions outline in Algerian Auditing Standard No 230. Consequently, the standard is not widely applied and relid upon.